Method for identifying the strength characteristics of concrete of a reinforced concrete crossbar during heating under conditions of fire - Pozdieiev, Serhii; Nekora, Olga; Fedchenko, Svitlana; Zaika, Nataliya; Shnal, Taras; Subota, Andriy; Nesukh, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2023)
This paper proposes a method that makes it possible to study the patterns of changes in the concrete strength of reinforced concrete crossbars depending on the heating temperature under fire conditions by interpreting the results of their standard fire tests. For the implementation of this method, it is proposed to use similar data obtained using mathematical modeling based on the finite element method and given material properties, including the curve of concrete strength reduction recommended by the guidelines, as data included in the set of measurement results during fire tests depending on temperature. Such data are time dependences of temperature indicators at individual cross-section points and time dependence of the maximum deflection of the crossbar. The article proposes an interpolation method that makes it possible to set the temperature at any point of the section based on the approximation of the isotherms by parabolas with a variable indicator of their power. A method based on the mathematical interpretation of temperature indicators obtained using the proposed interpolation method and the curve of the dependence of the maximum deflection on time using a deformation model for describing the stress-strain state is proposed to identify the dependence of the concrete strength of reinforced concrete crossbars. The work also shows that the results obtained using the proposed method of identifying concrete strength reduction coefficients are adequate as their relative error is on average no more than 7 %. Based on the results, the possibility of its application to study the regularities of the decrease in the strength of reinforced concrete crossbars under fire conditions has been proven